Piecing Together the Meaning of “Dirty Work” - Torelli, Julian (Qualitative Sociology Review, 2020)
I reflect upon Dr. William Shaffir’s influence on my approach to ethnographic research and my study of homeless shelter workers. Dr. Shaffir introduced me to his own brand of the craft of qualitative field work, but also introduced me to important sociologists and ideas in the symbolic interactionist tradition. Most central was Everett C. Hughes’ notion of “dirty work,” which helped shape my research focus. Building from Hughes’ concept, but expanding it with Shaffir and Pawluch’s (2003) social constructionist approach to occupations, I was better able to conceptualize the process of how workers themselves piece together the meaning of “dirty work.” Beyond gaining these conceptual insights, I also reflect on Dr. Shaffir’s teaching philosophy of qualitative methods, that is, the importance of learning by doing. I conclude with some thoughts regarding Shaffir’s perspective on the wider ethnographic task of describing, in situ, members’ understandings and definitions. Following Everett Hughes, I call on interactionists to give more attention to “dirty work” as a generic and transcontextual process.